Validity And Reliability of A Digital Intervention Combining Acceptance And Commitment Therapy And Therapeutic Relationship For Posttraumic Stress Disorder In Post-Surgery Patients - Muhad Sayyid, Farida; Wahid al-Jabri, Mushir Abdul; Wahidin, Wahidin (Advances In Social Humanities Research, 2024)
Digital interventions offer a promising approach to mental health care, especially for conditions such as post-traumatic stress disorder (PTSD) in postoperative patients. This study aims to assess the validity and reliability of the combined digital interventions of Acceptance and Commitment Therapy (ACT) and Therapeutic Relationship (TR). Psychometric evaluation was carried out involving 30 post-operative patients diagnosed with PTSD at a government hospital in Kebumen , Indonesia. Participants were randomly assigned to an intervention group receiving digital ACT and TR treatment or a control group receiving standard care. The validity of the intervention was assessed using measures of content and construct validity, while reliability was evaluated using internal consistency and test-retest reliability. The digital intervention demonstrated strong content validity, with expert review resulting in a Content Validity Index (CVI) of 0.92. Construct validity was supported by a significant correlation between change in PTSD symptoms and a measure of psychological flexibility (r = 0.68, p < 0.01). The intervention demonstrated high internal consistency (Cronbach's alpha = 0.87) and strong test–retest reliability ( Intraclass Correlation Coefficient [ICC] = 0.85). The combined digital intervention of ACT and TR is a valid and reliable tool for treating PTSD in postoperative patients. Its psychometric properties support its use in clinical settings, and further research should explore its efficacy and effectiveness in larger populations.